Prevention of pathological syndromes and post-morbidity rehabilitation of patients with heavy surgical infection on the basis of the complications development prediction index - S. V. Kemerov; V. M. Vorobjev; M. R. Karpova; M. M. Solov᾿ev; G. Tz. Dambaev (Бюллетень сибирской медицины, 2018)
Purpose of the study: working out an easy-to-use complication development index (CDI), designing a program for post morbidity rehabilitation of patients with surgical infection to improve the results of its treatment and reduce lethality.Materials and methods. A retrospective results analysis of treatment of 320 patients for purulent peritonitis and abdominal sepsis was carried out, including 268 patients (the comparison group) and 52 (the core group) with whom the complications development index was calculated. While studying this group of patients, the same protocol was used to prevent and treat complications on the basis of a complex individual program. In the comparison group, the patients were divided according to the severity of their condition in compliance with generally accepted clinical criteria: medium-heavy (98), severe (86) and extremely severe (84 patients, respectively).We have studied general clinical and biochemical indices, as well as the results of instrumental studies of the function of vital organs and body systems. The following indices were calculated:  the prothrombin index; the integral index of thromboelastography (IIT), J = [R (min) × K (min)] : mA (mm), where R is the clotting time, K is the clot formation time, mA is the clot density); the general condition severity APACHE II (Acute physiology and chronic health evaluation); the degree of organ dysfunction SOFA (Sepsis organ failure assessment); leukocyte index of intoxication (LII). The PIRO concept (predisposition, infection, response, organ dysfunction) was used for clinical interpretation of the received research results.Results. The prediction index of complications of surgical infection was proposed. It is based on the results of clinical analysis the results of patient treatment and calculated by using the severity of the underlying pathological process, as well as the number of concomitant diseases, pathological syndromes and aggravating factors.  As a result of the complication development prediction index use along with the implementation of the complex program for prevention and treatment of complications, the number went down from 50% to 90% in different groups under observation.